Social media usage and civic engagement among Indonesian digital natives: An Analysis - Tarsidi, Deni Zein; Suryadi, Karim; Budimansyah, Dasim; Rahmat, Rahmat (Universitas Negeri Yogyakarta, 2023)
This study aims to identify the relationship between social media use and civic engagement among digital natives in Indonesia using the Grounded Theory method. The study involved 15 digital natives aged 18-24 who actively use social media, selected through a purposive sampling technique. The analysis in this study used NVivo version 12 Plus for MacBook. The study results show that social media use plays a vital role in the civic engagement of digital natives in Indonesia. The participants stated that social media use could help increase their awareness and knowledge about social and political issues in Indonesia and enable them to participate in related activities. In addition, the study also shows that social media use can facilitate interaction and discussion among individuals with different views, which ultimately can deepen their understanding and experience of social and political issues in Indonesia. However, this study also identifies some challenges and obstacles in using social media for civic engagement. One is the authenticity and credibility of information disseminated on social media, which can influence individuals' views and opinions on an issue. Based on these findings, this study recommends improving digital literacy and information verification skills for digital natives in Indonesia.